Health-Related Quality of Life among Patients with Coronary Artery Disease: A Post-Treatment Follow-Up Study in Iran - Shahram Tofighi; Aliasghar Ahmad Kiadaliri; Jamil Sadeghifar; Mehdi Raadabadi; Jahanara Mamikhani (Cardiology Research and Practice)
Objective. To examine the changes in health-related quality of life (HRQoL) in patients with coronary artery disease (CAD) in terms of age, gender, and treatment strategy in Iran. Methods and Materials. Forty-nine patients responded to the Iranian version of the 36-item short form (SF-36) questionnaire to evaluate the HRQoL at first and third year after treatment. The paired and independent Wilcoxon rank-sum tests were used for within and between comparisons, respectively. Multivariate regression analysis was used to analyze the predictors of changes at HRQoL. Results. In general, during followup, the mental component summary scale improved, and the physical component summary scale declined. The results of multiple regression showed that the score at the first year post-treatment was the main predictor of HRQoL at follow up. Moreover, after adjusting for other covariates, receiving PTCA and being at older age were related to lower scores at followup, but these were not statistically significant in most cases. Conclusion. The HRQoL significantly changed from one to three years after treatment in patients with CAD. While, the physical health deteriorated during two-year follow up, mental health improved at the same time period. Generally, there were no significant differences at changes of HRQoL in terms of treatment, age, and gender.